Internalisasi Pendidikan Agama Bagi Remaja Melalui Majlis Ta’lim - Sanusi, Ahmad; Hamdanah, Hamdanah; Surawan, Surawan (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2021)
This article is the result of observations in Darussalam Danu roasted that there are special security studies carried out specifically for adolescents. This study was carried out in an effort to provide spiritual oases for young people in the midst of global challenges. This study was aimed at 1) grabbing the internalization process of adultery education of adolescent education through the Ta'lim Assembly and 2) displacing supporting factors and the inhibition of internalization of the values of the United Darussalam adolescent religion. The research uses the descriptive analysis method, development technique of collecting in the form of interviews, observation, and documentation. The subject in this study was an ustadz who taught at the Ta'lim Assembly, while informants were teenagers, adolescents who attended Majlis Ta'lim, community leaders, and peers. Informant complaints using purposive sampling. Data application techniques use triangulation of sources and techniques. The reason for data analysis includes reduction, displaying, and verification. The results of the study represented that 1) internalization of adultery education of adolescent education to instill the tilapia of religious values to adolescents, the method was used cheap modeling model and demonstration, data on the values of religion, worship, and morality. 2) Popular factors include the capacity of qualified teachers and communities. Meanwhile, inhibitory factors include the influence of negative association of adolescent associations and limited facilities of Majlis Ta'lim.